2016
DOI: 10.22502/jlmc.v4i2.101
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Assisted Vaginal Delivery in Singleton Term Pregnancies: Short Term Maternal and Neonatal Outcome in a Tertiary Hospital of Nepal

Abstract: Introduction: Other than cesarean delivery, assisted vaginal delivery is an alternative procedure for delivery in emergency obstetrics. Presently, vacuum delivery has gained more popularity than forceps for operative/ assisted vaginal delivery, when and where indicated, with success as well as lesser neonatal and maternal complications. This study was done to estimate the short term maternal and fetal morbidity/mortality due to vacuum assisted vaginal delivery.   Methods:  A prospective observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Contradicting the current study, Shrestha BK et al stated that prolonged second stage of labor followed by fetal distress (19.2%), poor maternal effort (9.6%) and to shorten the second stage of labour (8.6%) respectively, were the commonest indications for application of instruments. 25 Non descent of head in second stage of labour contributed to the largest number (77.1%) undergoing CS, similar to the study done by Babre VM et al where non-descent of the head was the second most common indication leading to CS. Non descent of head in both these studies can be credited to CPD or to DTA.…”
Section: Cesarean Section or Instrumentalsupporting
confidence: 84%
“…Contradicting the current study, Shrestha BK et al stated that prolonged second stage of labor followed by fetal distress (19.2%), poor maternal effort (9.6%) and to shorten the second stage of labour (8.6%) respectively, were the commonest indications for application of instruments. 25 Non descent of head in second stage of labour contributed to the largest number (77.1%) undergoing CS, similar to the study done by Babre VM et al where non-descent of the head was the second most common indication leading to CS. Non descent of head in both these studies can be credited to CPD or to DTA.…”
Section: Cesarean Section or Instrumentalsupporting
confidence: 84%
“…Tis study revealed a postpartum hemorrhage rate of 6.4%. Tis fnding was consistent with the study conducted in Jimma Medical Centre (3.3%), tertiary hospital of Mumbai, India (4.01%), Lumbini Teaching Hospital of Nepal (3.8%), and Amino Kano Hospital, Nigeria (9.5%) [14,[17][18][19]. However, this study's result of postpartum hemorrhage rate was lower than that of the University Hospital of Port, Nigeria (42.3%) [20].…”
Section: Discussionsupporting
confidence: 89%
“…There was one (0.96%) early neonatal death due to meconium aspiration syndrome. 20 Jason B et al in USA found that maternal morbidity among nulliparous women who underwent vacuum assisted delivery was 31%, third and fourth degree perineal tear was 16%, infections were 10%, lacerations were 5%, hemorrhage was 5% and < 1% had to stay in the hospital for more than 5 days. 19 Neonatal morbidity for vacuum assisted vaginal births in California between 2008 to 2012 was 13.3%.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with the study done by Chaudhari et al, Jason B et al, and Shresta et al except the neonatal morbidity rate which is less in our study, compared to few studies as even the experience, techniques of vacuum application and facilities at the intra-natal period make an impact in prevention of the complications. 8,[18][19][20] Chaudari P et al, in Uttarakhand found that in vacuum assisted deliveries 68% women needed episiotomy, 9% had perinial tear, 3% had vaginal / periurethral tear, 1% had post partumhemorrage and 1% needed blood transfusion. Morbidities of the newborns were 13% had NICU admissions, 18% neonates had cephalhematoma, 13% had hyperbilirubinemia, 11% had bruising, 5% had convulsions, 5% had feeding difficulties and 1% had irritability.…”
Section: Discussionmentioning
confidence: 99%